Social Business Postulates: From Traditional to Strategic Approach to CSR in Bulgaria (UNWE Yearbook, 2014)
Corporations increasingly adopt socially responsible actions, activities, policies and processes. The current study presents in a systematic way the aspects of corporate social responsibility (CSR), diversity of practices applied, status and trends in socially responsible behaviour of business in Bulgaria.Based on theoretical discussion on the concept of CSR and research done by an university project “CSR – a part of the European social practices in Bulgaria” in the study is derived the main research question: Do companies operating on the Bulgarian market implement strategic approach to CSR?Because CSR has been conceptualized in so many ways, the answer to the research question contributes to a better understanding of CSR, in particular by providing empirical evidence of current CSR practices in Bulgaria (websites research of the companies, operating on the Bulgarian market as well as results of an empirical study of business organizations in Bulgaria).